The Sound studies reader - Sterne, Jonathan (Routledge, 2012)
"The Sound Studies Reader is a groundbreaking anthology blending recent work that self-consciously describes itself as 'sound studies' with earlier and lesser known scholarship on sound. The collection begins with an introduction to welcome novice readers to the field and acquaint them with key themes and concepts in sound studies. Individual section introductions give readers further background on the essays and an extensive up to date bibliography for further reading in 'sound studies' make this an original and accessible guide to the field"--Publisher.